Differences in Bleeding Episodes in Severe Hemophilia A Based on Nutritional Status - Wenny Simamora; Susi Susanah; Amaylia Oehadian (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Hemophilia A is a congenital bleeding disorder caused by the deficiency of coagulation factor VIII and is characterized by joint bleeding, especially in weight-bearing joints. An excess weight may cause bleeding in hemophilia due to increased joint tension. This study aimed to determine the differences in bleeding episodes between severe hemophilia A patients with and without excess weight.Method: A comparative observational analytic study was conducted in March-November 2019 using a cross-sectional design. Subjects were patients with severe hemophilia A registered in the Indonesian Hemophilia Society Association in West Java and had had severe hemophilia A for at least two years old with complete data on date of birth, height, weight, and bleeding intensity. Subjects were divided into groups with excess weight (excess weight) and without excess weight (non-excess weight). Nutritional status in adults was determined based on age-specific percentile BMI. Bleeding episodes were determined as frequency of bleeding in one year. The Mann-Whitney statistical test was used to observe the difference between groups.Result: Of 226 severe hemophilia A patients registered, only 155 patients were included. Of these, 121 patients did not have excess weight and 34 had excess weight. The median bleeding episodes of in the non-excess weight and excess weight groups were 24(1-48) and 24(8-48), respectively (p=0.761).Conclusion: There is no difference in bleeding episodes Between severe hemophilia A patients with excess weight and without excess weight. However, good nutrition education needs to be provided to these patients since excess weight may increase bleeding in joints.